Transcriptome and Lipid Metabolomics-Based Discovery: Glycyrrhizic Acid Alleviates Tripterygium Glycoside Tablet-Induced Acute Liver Injury by Regulating the Activities of CYP and the Metabolism of Phosphoglycerides - Shi, Qiaoli; Wang, Qixin; Chen, Jiayun; Xia, Fei; Qiu, Chong; Li, Min; Zhao, Minghong; Zhang, Qian; Luo, Piao; Lu, Tianming; Zhang, Ying; Xu, Liting; et al. (Frontiers in Pharmacology, 2022)
Background: Glycyrrhizic acid (GA) has been reported to be liver protective, however, the characters and underlying mechanisms of GA against tripterygium glycosides tablet (TGT)-induced acute liver injury remain unelucidated. Hypothesis/Purpose: We assumed that GA could relieve TGT-induced acute liver injury by regulating liver function related genes and lipid metabolites. Study Design: TGT-induced acute liver injury models were constructed in vivo and in vitro respectively. Then the liver protective effect and mechanisms of GA were investigated by a combination of transcriptome, lipid metabolomics and experimental validation. Methods: Intraperitoneal injection of GA was given in advance for 6 successive days. Then, the TGT-induced acute liver injury model was constructed by single oral administration of TGT at 270 mg/kg except the normal group. All animals were sacrificed 18 hours later. The serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), total bilirubin (TBIL), glutathione peroxidase (GSH-PX) and superoxide dismutase (SOD) were quantified. Liver tissues were used for pathological changes observation by hematoxylin-eosin (HE) staining and selected for transcriptome and metabolome sequencing. The underlying mechanisms was analyzed and further validated both in vivo and in vitro. Results: Pre-administration of GA markedly decreased the serum concentrations of AST, ALT, ALP and TBIL whereas increased those of SOD and GSH-Px, improved liver morphology of mice with TGT-induced acute liver injury. In addition, GA significantly increased gene level of Cyp2b13, Cyp2c69, Cyp3a16, Cyp3a44, Fmo3 and Nipal1. Differentially accumulated metabolites were screened and classified as phosphatidylcholine (PC) and phosphatidylethanolamine (PE). The in vitro results indicating that pre-administration of GA markedly alleviated the inhibitory effect of TGT on BRL-3A activity. Conclusions: This study combined transcriptome, lipid metabolomics and experimental validation offers the convincing evidence that GA alleviates TGT-induced acute liver injury partially by regulating the activities of CYP and the metabolic of PC and PE.